2017
DOI: 10.1002/pros.23430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of five‐tiered Gleason grade groups on prognostic prediction in clinical stage T3 prostate cancer undergoing high‐dose‐rate brachytherapy

Abstract: Stage T3a patients with grade groups 4/5 and stage T3b with grade group 4 had fairly low PCSM risk. Approximately one of four patients among stage T3b patients with grade group 5 showed PCSM after combined HDR-BT and EBRT with long-term ADT. Stage T3b patients with grade group 5 may have a greater risk for PCSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…Other poor prognosis factors, such as a high Gleason score (≥ 8), high tumor infiltration on prostate biopsy and extracapsular extension were also identified as poor prognostic factors in several surgical and BT series [8,10,14,49,59], as well as in our series in univariate analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Other poor prognosis factors, such as a high Gleason score (≥ 8), high tumor infiltration on prostate biopsy and extracapsular extension were also identified as poor prognostic factors in several surgical and BT series [8,10,14,49,59], as well as in our series in univariate analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Our data partly concurred with their data because a significant threshold to separate PCSM with the highest hazard ratio was obtained between T3a and T3b and Gleason score sum 8 and 9, but not in iPSA ( Table 3 ). Tsumura et al reported similar results that stage T3b patients with grade group 5 may have a greater risk for PCSM [ 20 ].…”
Section: Discussionmentioning
confidence: 88%
“…A total of eight studies were selected for inclusion in the meta-analysis, all of which were retrospective series classified as Level 4 evidence [14] , [20] , [21] , [22] , [23] , [24] , [25] , [26] . Four reported data from a single institution, while the remaining four were multi-institutional.…”
Section: Resultsmentioning
confidence: 99%